Spatially and Sequentially Heterogeneous Discounts of Distressed Property Values in Cuyahoga County, Ohio. Issue 4 (4th July 2017) - Seo, Youngme; Mikelbank, Brian
Abstract: One of the most persistent public policy debates is over the aftermath of the foreclosure crisis and its continuing impact on housing markets. Distressed properties – including foreclosure and real estate-owned properties – tend to be sold at much lower prices than nearby comparable properties, often pulling down both surrounding property values and neighborhood morale. Recent findings show that these discounts for distressed properties are associated with various factors, but three important dimensions of these discounts remain relatively unexplored. First among these is the degree of variation in these discounts, even within the same regional market. Second is how discounts vary through the typical sequence of the distressed property transaction cycle. The final factor is the nature by which discounts vary according to the market participants – are the buyers/sellers individuals or institutions? This study examines these major factors affecting discounts, and estimates the spatially and sequentially heterogeneous discounts for distressed properties in the housing submarkets of Cuyahoga County, Ohio. Findings indicate that the discounts of distressed properties in the strong and weak submarkets substantially vary based on all three of these previously overlooked factors, yielding a more complex and nuanced housing context for practitioners and policymakers to consider.